Peeking at the Cataloguing Modules of Popular Open-Source ILS: Evergreen vs Koha - Sarma, Gautam Kumar; Das, Jitu Mani; Singh, Anuj Kumar (Journal of Information and Knowledge, 2024)
A library catalogue is a list of all the holdings of a library or group of libraries. It may include books, non-book materials, e-books, grey literature, etc. An Integrated Library System (ILS) is incomplete without a well-designed cataloguing module. The creation and management of library catalogues require expertise. Globally, there are two popular open-source ILS, namely Evergreen and Koha, with regular updates and significant versions acquired by several libraries worldwide. Both Koha and Evergreen provide intuitive cataloguing interfaces that make it easy for library professionals to add and manage bibliographic information. The present study aims to discuss the cataloguing module of these two open-source ILS, which is based on a review of prior research, information from the ILS’s website, community and demo servers on the web, and the researchers’ hands-on experience with a local installation.